Studies on Aromatic Amide of Root of Carissa caranadas Linn - MALIPATIL, MALLIKARJUN; CHANDRA, RAMESH; RAMESH, H. (Asian Journal of Chemistry, 2010)
The objective of the work is to study the chemical constituents of benzene extract of root of Carissa carandas Linn. Phytochemical investigation conducted on root revealed the presence of carbohydrates, alkaloids, flavanoids, saponins, steroids and fatty acids. The aromatic amide was detected in benzene extract and methanol extract of the root. The extracts were carried out by Soxhlet extractor and the yield of benzene extract was 2.5 %. TLC study of benzene extract showed the presence of 5 spots, out of which one spot was identified as aromatic amide. The present study deals with chemical investigation of benzene extract of root of Carissa carandas Linn. The five compounds were separated by column chromatography using benzene:ethyl acetate:chloroform (4:2:1). TLC study of separated compounds with Rf value 0.45 (B1), 0.58 (B2), 0.93 (B3), 0.62 (B4) and 0.59 (B5). From UV, IR, 1H NMR and LC-MS analysis of the compound B5, it could be characterized as aromatic amide.